Nucleotide inhibition of the pancreatic ATP-sensitive K(+) channel explored with patch-clamp fluorometry - Usher, Samuel G (eLife, 2020)
Pancreatic ATP-sensitive K(+) channels (K(ATP)) comprise four inward rectifier subunits (Kir6.2), each associated with a sulphonylurea receptor (SUR1). ATP/ADP binding to Kir6.2 shuts K(ATP). Mg-nucleotide binding to SUR1 stimulates K(ATP). In the absence of Mg(2+), SUR1 increases the apparent affinity for nucleotide inhibition at Kir6.2 by an unknown mechanism. We simultaneously measured channel currents and nucleotide binding to Kir6.2. Fits to combined data sets suggest that K(ATP) closes with only one nucleotide molecule bound. A Kir6.2 mutation (C166S) that increases channel activity did not affect nucleotide binding, but greatly perturbed the ability of bound nucleotide to inhibit K(ATP). Mutations at position K205 in SUR1 affected both nucleotide affinity and the ability of bound nucleotide to inhibit K(ATP). This suggests a dual role for SUR1 in K(ATP) inhibition, both in directly contributing to nucleotide binding and in stabilising the nucleotide-bound closed state.